Raspberry-structured silver-carbon hybrid nanoparticle clusters for high-performance capacitive deionization - Chiang, Meng-Ting; Tu, Yi-Heng; Chiang, Hsin-Li; Hu, Chi-Chang; Tsai, De-Hao (Desalination, 2021)
An aerosol-based synthetic approach, in combination with a real-time characterization method using differential ion-mobility analyses coupled to temperature-programmed Fourier-transform infrared spectroscopy (DMA/TP-FTIR), was demonstrated for the development of raspberry-structured Ag‑carbon hybrid nanoparticle clusters (Ag-C-NPC). Physical size, number concentration, and compositions of the Ag-C-NPC were shown to be successfully characterized directly in the aerosol state on a quantitative basis. Remarkable high salt adsorption capacity (15.6 mg/g), good charging/discharging stability, and low requirement of cell voltage were attainable by using the Ag nanoparticle-decorated carbon nanoparticle clusters as the positive electrode material. This work provides a proof of concept of using the aerosol-based synthesis, with the support of in-situ characterization, for the development of AgC nanocomposite clusters to achieve high CDI performance. The method also shows promise for the tuning of the material properties of Ag-C-NPC for the optimization of the CDI capacity and cyclic stability useful for a variety of the water desalination applications (e.g., brackish water). [Display omitted] •Ag-carbon nanoparticle clusters as positive electrode via aerosol-based synthesis.•Direct gas-phase coupled characterization supports the aerosol-based synthesis.•Successful quantitative characterization of the Ag-C-NPC in aerosol state.•Remarkable high capacity (15.6 mg/g) and stability with a low cell voltage.